Experiências pedagógicas de uma professora em formação: contribuições do Programa Institucional de Bolsas de Iniciação à Docência (PIBID) e Programa Residência Pedagógica do Instituto de Estudos Costeiros - LOBÃO, Maysa Melo (2022)
The present Course Conclusion Work is formed by the combination of works developed during institutional programs. Its structure consists of two chapters and a conclusion. Chapter I presents: “GAME OF DNA: A BOARD GAME PROPOSAL FOR BASIC GENETICS TEACHING, IN THE THIRD YEAR OF HIGH SCHOOL”, was prepared during the course of Genetics in the Licentiate in Biology course and modified during the performance at PIBID. Chapter II presents “EMERGENCY REMOTE TEACHING: THE REALITY OF PRACTICE BEHIND THE VIRTUAL WORLD”, was developed during the internship at PRP, in a third year high school class, during the emergency remote teaching period, caused by the COVID-19 virus. The opportunity to have contact with the practice and discuss it during the training of the licentiate is fundamental for the professional profile that is being created. The PIBID and PRP programs successfully carry out this exercise. Based on the work developed within the programs, the mutual exchange of knowledge between residents and preceptor teachers is observed to be significantly for both, and the need for public policies to increasingly invest in the improvement of training is emphasized. practice in undergraduate courses.